2013
DOI: 10.1007/978-3-642-40763-5_23
|View full text |Cite
|
Sign up to set email alerts
|

Accurate Bone Segmentation in 2D Radiographs Using Fully Automatic Shape Model Matching Based On Regression-Voting

Abstract: Recent work has shown that using Random Forests (RFs) to vote for the optimal position of model feature points leads to robust and accurate shape model matching. This paper applies RF regression-voting as part of a fully automatic shape model matching (FASMM) system to three different radiograph segmentation problems: the proximal femur, the bones of the knee joint and the joints of the hand. We investigate why this approach works so well and demonstrate that the performance comes from a combination of three p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 13 publications
1
33
0
Order By: Relevance
“…In [10], we demonstrated that the proposed method generalises well across medical application areas, achieving what we believe to be the best published results for proximal femur and knee joint segmentation. For facial feature point detection, we would like to point out that although the approach was demonstrated on frontal faces, it would be equally applicable to non-frontal faces, given a suitable training set. "…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…In [10], we demonstrated that the proposed method generalises well across medical application areas, achieving what we believe to be the best published results for proximal femur and knee joint segmentation. For facial feature point detection, we would like to point out that although the approach was demonstrated on frontal faces, it would be equally applicable to non-frontal faces, given a suitable training set. "…”
Section: Discussionsupporting
confidence: 53%
“…Preliminary outputs of this work were presented in [9] for introducing RFRV in the CLM framework and in [10] for analysing what properties of RFRV contribute to its highly accurate and robust performance. This paper expands on the latter in various ways: (i) We provide a more detailed description of RFRV and how it is used in the CLM framework.…”
Section: Introductionmentioning
confidence: 99%
“…Each model uses regression-voting trees to predict point displacements from patches of image texture and constrains the points using a shape model. The algorithm has been used previously to find hips and knees 16 from radiographs.…”
Section: Object Detection and Shape Model Matchingmentioning
confidence: 99%
“…A key first step in such analysis is often locating the outlines of the structures of interest. Recently, it has been shown that robust and accurate annotations can be automatically obtained using shape-based model matching algorithms [2,4,8,9]. Unfortunately, building such models requires accurate annotation of large numbers of points on several hundred images.…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that RFRV-CLMs can successfully be applied as part of a fully automatic segmentation system to accurately and robustly segment bone shapes in 2D radiographs [8,9]. In this paper, we explore the effect of different annotation schemes on RFRV-CLM performance.…”
Section: Introductionmentioning
confidence: 99%